سرسید اور علامہ محمداقبال کے علمی و فکری روابط: SAME VIEWS OF SIR SYED AND ALLAMA MUHAMMAD IQBAL IN SCIENTIFIC AND INTELLECTUAL (Al-Aasar, 2025)
Sir Syed Ahmad Khan (1817-1898) wanted modern education for Muslims. He wanted Muslims to develop like other nations. This was possible only when Muslims were familiar with modern sciences. The same message of Sir Syed was carried forward by Allama Muhammad Iqbal (1877-1938). He wrote a poem 'Syed ki Loh-e-Turbat' included in 'Bang-e Dara', which marks Sir Syed's academic and literary thoughts. Sir Syed's movement had three angles (religion, education, politics). Iqbal has presented the trial of these three angles in the poem. Both the great leaders have the same intellectual and intellectual views.